SHOOTING PERFORMANCE DID NOT CHANGE IN ELITE WOMEN’S NATIONAL BASKETBALL TEAMS FROM 1995 TO 2011 - Kreivyte, Rasa; Emeljanovas, Arunas; Sporiš, Goran; Knjaz, Damir; Vučković, Goran; Milanović, Zoran (Annales Kinesiologiae, 2013)
<span style="line-height: 115%; font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: Calibri; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">Performance indices, i.e. model characteristics, quantitative and qualitative indices of a shot made at the basketball match, are a part of the system of criteria that allow one to objectively determine and evaluate the readiness of basketball teams and the quality of their performance. The aim of this research was to identify and evaluate changes in the key quantitative and qualitative indicators of shooting for the best European women’s basketball national teams between 1995 and 2011. The data from official statistical documents for the 1995, 1997, 1999, 2001, 2003, 2005, 2007, 2009 and 2013 European women’s basketball championships were collected and statistical analyses (mean, standard deviation) of 608 cases were used. It was ascertained that the number of scores in one match of the European championship of the eight best women’s basketball teams decreased from 69 to 65 points. The number of shots from close and middle distances dropped sharply ─from 51 to 43 points in a match, however, their accuracy remained similar ─ between 42 and 43 %. The number of long-distance shots increased dramatically, from 9 to 16 points in a match, their accuracy had a tendency to increase from 29 to 33 %. The number of free throws decreased significantly ─ from 26 to 17 points in a match, but their accuracy remained similar ─ between 71 and72 %.